(3JWHjbGJ (BAdobe Photoshops ((3GdbGgQIs (3KQj Oj ceHjhJQs, 2008)
(3cd LOjO HHQfGeL Gd (BPhotoshop (3JfejI GdegGQGJ GdafjI deSJNOej Gd(BPhotoshop (3EfTGA GdQShe GdeJMQcI HGSJNOGe Gd(BIImage Ready (3JUeje ehGbY GdEfJQfJs
(3Gbhj HQfGeL JYdje HGddZI GdYQHjI aj GdhWf GdYQHjs
(3NGUjI GdJTZjd GdJdbGFj ddHQfGeL hGSJNOGe GdUhJ hGdUhQI CKfGA YedjI GdTQM ef NdGd GdJfajP GdaYdj ddJWHjbGJs
1
Keywords: Adobe Photoshop -- (3ehGO SeYjI hHUQjIs; (3HQGeL GdMGShHs -- (3JYdes -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG cHGQs -- (3ehGO SeYjI hHUQjIs